2021
DOI: 10.3390/en14154436
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Analysis Comparison of Three Air-Cooling Systems in Terms of Thermal Comfort, Air Quality and Energy Consumption for School Buildings in Mediterranean Climates

Abstract: Efficient air-cooling systems for hot climatic conditions, such as Southern Europe, are required in the context of nearly Zero Energy Buildings, nZEB. Innovative air-cooling systems such as regenerative indirect evaporative coolers, RIEC and desiccant regenerative indirect evaporative coolers, DRIEC, can be considered an interesting alternative to direct expansion air-cooling systems, DX. The main aim of the present work was to evaluate the seasonal performance of three air-cooling systems in terms of air qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The COP could be increased by up to 18%. Romero-Lara et al [100] established a comparison between three air-cooling systems in which it appears that desiccant cooling systems consume from three to fifteen times less energy than a conventional VC system depending on the climate zone. Regarding environmental impact, they concluded that desiccant systems could be an alternative to traditional VC systems to reduce CO 2 emissions by 68-78% in the warmest zones.…”
Section: Desiccant Systemsmentioning
confidence: 99%
“…The COP could be increased by up to 18%. Romero-Lara et al [100] established a comparison between three air-cooling systems in which it appears that desiccant cooling systems consume from three to fifteen times less energy than a conventional VC system depending on the climate zone. Regarding environmental impact, they concluded that desiccant systems could be an alternative to traditional VC systems to reduce CO 2 emissions by 68-78% in the warmest zones.…”
Section: Desiccant Systemsmentioning
confidence: 99%